(untitled) (Journal of Civil Engineering Researchers, 2022)
In recent years, the use of lightweight concrete in the world has grown exponentially. The reason is the lightening of the building and as a result the reduction of dead load and seismic force on the structures as well as better performance in terms of thermal insulation and energy saving. Therefore, it is necessary to study the potentials of using lightweight concrete in the construction industry. In this article, which is the result of analytical and experimental results about a special type of lightweight aggregate called Leica, the aim is to first achieve a lightweight concrete mixing design that has the necessary conditions as lightweight structural concrete. In this paper, during laboratory research, using Leica concrete grain style with an approximate compressive strength of 20 MPa and a specific gravity of approximately 1800 kg / m3 was obtained. Secondly, we investigated the structural behavior of concrete beams made with Leica lightweight aggregate experimentally and numerically. For this purpose, the first 5 concrete beams were made and examined in the laboratory, and finally, using ABAQUS finite element software, a suitable model was found to model such beams, which is in good coordination with the laboratory results. The compatibility of the results obtained from the modeling with the laboratory results is proof of the accuracy of the constructed model.